DECONSTRUCTION CONCEPT DESIGN OF EXHIBITION CENTER IN DEPOK CITY WITH DISJUNCTION INTERPRETATION (DIMENSI: Journal of Architecture and Built Environment, 2022)
Contemporary urban condition always evoke a series of impressive artistic architectural responses with an understanding that is no longer interested in unity, but also accepts the fragmentation of certain elements. When considering contemporary problem-solving efforts with design-based responses, it will also link design with research to find out solutions. This research focuses on conveying critical reflections on how to interpret the deconstruction concept design of Exhibition Center in Depok City by questioning the new design definition based on research by design. The understanding of the deconstruction concept uses Bernard Tschumi's disjunction theory as a methodological process based on the visualization exploration. Disjunction interpretation helped to define the new Exhibition Center design in Depok City as urban generator. It is hoped that this research would be beneficial in guiding to considering the "built language" of design as an act of research that are open to possibilities based on thought and experience.